(3JjSjQ GdhUhd Edi efgGL GdCUhds - (3eMeO Hf eMeO NWjH GdcGedjIs; (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj , GdTjQGRj GdHjVGhj, CHh SYjO CHh GdNjQ fGUQ GdOjf,J (B685 (3g` s ((3Ydi Hf eMeO Hf GdJfhNi GdhaGFi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi aJM HJjSjQ GdhUhd Edi CUhd GdTQjYI GdZQGA hHYO abO jSQ Gddg GdcQje HGJeGe JjSjQ GdhUhd Edi efgGL GdCUhd s
(3BNQgG (B:s
(3HLhGR GdJbdjO hcdGe GdCUagGfi ai TQMg ddefgGL jDeF Zdi eG TQMJg Ydjg hgh CbQH eG Hjf Hg GdfXQ hjMJed ZjQ Pdc hGddg CYde s
(3Ydjg JedcGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B298s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs